HUBUNGAN MASA KERJA DAN SIKAP KERJA DENGAN KELUHAN CARPAL TUNNEL SYNDROME PADA PEKERJA PENENUN ULOS DI GALERI ULOS SIANIPAR MEDAN TAHUN 2020 - Isidorus Jehaman; Monika Julintina; Luci Riani Br Ginting; Sabirin Berampu (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Carpal tunnel syndrome is an eddy condition where the middle nerve is compressed in the wrist which results in parasthesia, numbness and muscle weakness in the hand. One nactor in the increasing number on carpal tunnel syndrome complaints is the outbreak on activities that use the hands especially those that carry out long periods on time. based on a preliminary study on 10 ulos weavers, there were 7 ulos weavers who had Carpal tunnel syndrome complaints in the norm on hand pain, tingling and numbness in the hands. The purpose on this study was to determine the relationship on work tenure and work attitude with complaints on carpal tunnel syndrome in ulos weaver workers at the Galery Ulos Sianipar Medan. The method in this study is an analytic observer research method with a cross sectional research approach. The respondents on this study are the ulos weavers in the Galery Ulos Sianipar Medan. Research instruments in the norm on questionnaires and measurement on phalen test data were analyzed by chi-square test. Based on the results on the study, the majority on ulos weavers experienced complaints on carpal tunnel syndrome as many as 34 people (65.4%). In this study it was nound that there was a relationship between work period (p = 0.003<0.05) with complaints on carpal tunnel syndrome, while work attitude (p = 0.399 >0.05) had no relationship with complaints on carpal tunnel syndrome. Suggestions nor ulos weaver workers are expected to take regular breaks by bending and straightening hands nor 3-5 minutes to reduce the risk on carpal tunnel syndrome